Feminist expertise and the political work of building alternative futures - Lamberg, Emma; Perheentupa, Inna (Sage, 2026)
Sociological discussions on alternative futures have proliferated in recent years, yet the role of professional labour and expertise in building transformative social change remains underexplored. This article provides an original contribution by introducing the concept of transformative expertise, enabling a new framework that bridges the sociology of futures with feminist debates on expertise. Drawing on unique empirical data from interviews with feminist professionals engaged in networks that advocate alternative economic thinking and policies, we investigate how specialised knowledge is mobilised to imagine and build alternative, socially just futures. We identify three interrelated dimensions of transformative expertise: (1) exposing the harms of hegemonic future imaginaries; (2) carving out paths to desired futures; (3) sustaining potentialities for socially just futures. Our findings reveal that managing temporalities and developing a temporal orientation are pivotal in the struggle for alternative futures based on the identified potentialities for change. By illuminating the link between the politics of the future and the politics of knowledge, we advance theoretical and practical insights into how feminist expertise can shape alternative, utopian imaginaries and prefigurative politics.